Worker Co-operatives and Spaces of Possibility: An Investigation of Subject Space at Collective Copies - Cornwell, Janelle (Antipode, 2012)
:  If we are to understand the organization and growth of capitalist space, should we not also seek to understand the organization and expansion of noncapitalist economic spaces? In contrast to methods employed by theorists such as Harvey, Smith and other geographers focused on capitalist space, the diverse economies framework opens up to investigation such noncapitalist spaces. In this paper, using Gibson‐Graham's “politics of possibility”, I explore the production of work space and time in a growing worker owned co‐operative copy shop in order to gain insight into the organization and growth of co‐operative space. I argue that, in this instance, co‐operative growth emerges from the transformative experience of workers having a say in their daily work lives, having equal authority to govern work space and time and to appropriate and distribute surplus.